Internationalization of Georgian Companies - Sarishvil, Davit; Shengelia, Mogeli (European Scientific Journal, ESJ, 2017)
Nowdays, people are interested in internationalization of markets and business. There are new companies on the market which from the start-up have the aim to internationalize. In general, they have not enough resources for internationalizition. In this topic we will discuss particular resources which should be internationalized and be part of international business. There are some types of such businesses, such as international entrepreneurial organization or born global companies. Of course, study of such companies should be started based on traditional strategies of market penetration, such as export strategy, licensing, etc. Afterwords, we will discuss new trends which help new-born companies to penetrate form the start-up into new marketns and increase their sales based on export. Such trend can be learning process estabilished in companies or experience of the managers who have operated in international markets. There is one type of research which indicates such trendes. This type of research is empirical analysis. There are good examples of such business. For example in Australia or Lithuania there are many businesses internationalized from the start. We will present results and factors from research which have been conducted in these countries. And finally, we will discuss Georgian market and companies which have already been nternationalized.